Mild Plasmodium falciparum Malaria following an Episode of Severe Malaria Is Associated with Induction of the Interferon Pathway in Malawian Children - Krupka, Malkie (American Society for Microbiology, 2012)
Infection with Plasmodium falciparum can lead to a range of severe to minimal symptoms, occasionally resulting in death in young children or nonimmune adults. In areas of high transmission, older children and adults generally suffer only mild or asymptomatic malaria infections and rarely develop severe disease. The immune features underlying this apparent immunity to severe disease remain elusive. To gain insight into host responses associated with severe and mild malaria, we conducted a longitudinal study of five children who first presented with severe malaria and, 1 month later, with mild malaria. Employing peripheral blood whole-genome profiling, we identified 68 genes that were associated with mild malaria compared to their expression in the severe malaria episode (paired Students t test, P < 0.05). These genes reflect the interferon (IFN) pathway and T cell biology and include IFN-induced protein transcripts 1 to 3, oligoadenylate synthetases 1 and 3, and the T cell markers cathepsin W and perforin. Gene set enrichment analysis identified Gene Ontology (GO) pathways associated with mild malaria to include the type I interferon-mediated signaling pathway (GO 0060337), T cell activation (GO 0042110), and other GO pathways representing many aspects of immune activation. In contrast, only six genes were associated with severe malaria, including thymidine kinase 1, which was recently found to be a biomarker of cerebral malaria susceptibility in the murine model, and carbonic anhydrase, reflecting the blood's abnormal acid base environment during severe disease. These data may provide potential insights to inform pathogenesis models and the development of therapeutics to reduce severe disease outcomes due to P. falciparum infection.